Heterogeneous SSTR2 target expression and a novel KIAA1549::BRAF fusion clone in a progressive metastatic lesion following 177Lutetium-DOTATATE molecular radiotherapy in neuroblastoma: a case report - Park, Se Whee Sammy; Fransson, Susanne; Sundquist, Fredrik; Nilsson, Joachim N.; Grybäck, Per; Wessman, Sandra; Strömgren, Jacob; Djos, Anna; Fagman, Henrik; Sjögren, Helene; Georgantzi, Kleopatra; Herold, Nikolas; et al. (Frontiers in Oncology, 2024)
In this case report, we present the treatment outcomes of the first patient enrolled in the LuDO-N Trial. The patient is a 21-month-old female diagnosed with high-risk neuroblastoma (NB) and widespread skeletal metastasis. The patient initially underwent first line therapy according to SIOPEN HRNBL-1 but was switched to second line treatments due to disease progression and she was finally screened for enrollment in the LuDO-N trial due to refractory disease. Upon enrollment, the patient received two rounds of the radiolabeled somatostatin analogue Lutetium-177 octreotate ( 177 Lu-DOTATATE), which was well-tolerated. Dosimetry analysis revealed a heterogeneous uptake across tumor lesions, resulting in a significant absorbed dose of 54 Gy in the primary tumor, but only 2 Gy at one of the metastatic sites in the distal femur. While initial treatment response showed disease stabilization, the distal femoral metastasis continued to progress, leading to the eventual death of the patient. Tissue analysis of the biopsies collected throughout the course of the disease revealed heterogeneous drug target expression of somatostatin receptor 2 (SSTR2) across and within tumor lesions. Furthermore, genomic profiling revealed a novel KIAA1549::BRAF fusion oncogene amplification in the distal femoral metastasis at recurrence that might be related with resistance to radiation, possibly through the downregulation of SSTR2. This case report demonstrates a mixed response to molecular radiotherapy (MRT) with 177 Lu-DOTATATE. The observed variation in SSTR2 expression between tumor lesions suggests that heterogeneous target expression may have been the reason for treatment failure in this patient case. Further investigation within the LuDO-N trial will give a more comprehensive understanding of the correlation between SSTR2 expression levels and treatment outcomes which will be important for advancing treatment strategies based on MRT for children with high-risk NB.